Academic integrity or academic misconduct? Conceptual difficulties in higher education and the potential contribution of student demographic factors - Rachel Harrad (Higher Education Research & Development, 2024)
Academic misconduct and academic integrity are issues of importance to Higher Education Institutions (HEIs). Phraseologies and practices may conflate unintentional mistakes with attempts to gain illegitimate advantage, with some groups potentially at higher risk. HEIs across the United Kingdom (UK) responded to a Freedom of Information Act (FOI) request, and provided data regarding their overall student demographics, the demographic details of their cases of referred and substantiated academic misconduct over a specific time period, as well as information about Turnitin. Available data were analysed with an estimated combined student population of 200,646 with an estimated 2718 students referred for academic misconduct. Analyses revealed some groups being referred out of proportion with their share of the student population, however, no significant differences were observed by demographic for substantiated cases. Most of the responding HEIs indicated Turnitin was used for both identification of misconduct and pedagogical purposes although some reported variations in use for pedagogy by department or module. Implications of the findings are considered. Limitations around available data are discussed and areas requiring more detailed consideration are identified.